Pengaruh Beban Kerja dan Kompensasi terhadap Kinerja Karyawan pada PT Pinang Witmas Sejati Klk Desa Mangsang - Rena Yanti; Roswaty Roswaty; Emilda Emilda (Universitas Batanghari Jambi, 2023)
The purpose of this study is to determine the effect of workload and compensation on employee performance at PT Pinang Witmas Sejati KLK. The type of research used is quantitative research by distributing questionnaires through the Google Form. Sampling using saturated sampling technique using the entire population of 68 respondents. Sources of data in this study were primary data and secondary data using a purposive sampling technique. The results of the t test analysis show that workload has a positive and significant effect on employee performance at PT Pinang Witmas Sejati KLK, with significant value 0.000 <0.05 and tcount > ttable (-2,066 > 1.669) then H0 is rejected H1 is accepted. Compensation also partially has a positive and significant effect on employee performance at PT Pinang Witmas Sejati KLK, with significant value 0.016 <0.05 and tcount > ttable (2.470 > 1.669) then H0 is rejected H1 is accepted. Then the results of the F test analysis (simultaneous) show that workload and compensation together have a positive and significant effect on employee performance at PT Pinang Witmas Sejati KLK, with significant value 0.000 < 0.05 and Fcount > Ftable (33.366 > 3.99). From the test results the coefficient of determination (R2) is 0.507. This shows that the magnitude of the contribution between the Workload variable and the Compensation variable on Employee Performance is 50.7%.